Biosorption of Cr (VI) using a bacterial biofilm supported on granular activated carbon and on zeolite - Lameiras, Sandra Raquel de Vasconcelos (2008)
Two mini-columns partially filled with granular activated carbon (GAC) and/or a natural zeolite, covered by a bacterial biofilm of Arthrobacter viscosus, were used in a continuous flow system to remove Cr (VI) from solutions with initial concentration of 70 mg/l and a working pH ranging between 4.5 and 5.5. Three different set-up’s were used: two columns in series filled GAC covered with a biofilm, two columns in series filled with zeolite covered with a biofilm and a column filled with GAC followed by another column filled with zeolite, both supports covered with biofilm. Comparatively, the biosorption system supported on GAC reaches similar removal values, 19%, as the one supported on the zeolite, 18%, but when these two beds are used in combination better performances are reached, i.e. 42% removal. The maximum uptake values ranged from 0.57 mgCr/gSupport to 3.58 mgCr/gSupport. The interactions between metal ions and functional groups on the cell wall surface of the biomass were confirmed by FTIR. GAC was regenerated with steam draughting and reused twice. The first regeneration caused a decrease in the removal capacity of 38% and the second regeneration caused a total decrease in the removal capacity of 76%.